Formation of a conceptual framework during the development of a patient‐reported outcome measure for early gastrointestinal recovery: phase I of the PRO‐diGi study - Baker, Daniel M.; Chapman, Stephen J.; Thomas, Benjamin D.; Thompson, Benjamin J.; Hawkins, Deborah J.; Arnott, Robert; Blackwell, Sue; Thorpe, Gabrielle; Harji, Deena P.; Jones, Georgina L.; Lee, Matthew J. (Colorectal disease, 2023)
AimPatients admitted to hospital for abdominal surgery often experience gastrointestinal dysfunction. Many studies have reported outcomes following gastrointestinal dysfunction, yet there is no unified definition of recovery or a validated patient‐reported outcome measure (PROM). The first stage of PROM development requires formation of a conceptual framework to identify key themes to patients. The aim of this study was to utilize semistructured interviews to identify core themes and concepts relevant to patients to facilitate development of a conceptual framework.MethodAdult patients admitted to hospital for major gastrointestinal, urological or gynaecological surgery, in an emergency or elective setting, were eligible to participate. Patients treated nonoperatively for small bowel obstruction were also eligible. Interviews were conducted by telephone, audio‐recorded, transcribed, coded and analysed using NVivo software by two researchers and reviewed by lay members of the steering group. Interviews continued until data saturation was reached. Ethical approval was gained prior to interviews (21/WA/0231).ResultsTwenty nine interviews were completed (17 men, median age 64 years) across three specialties (20 gastrointestinal, six gynaecological, three urological). Two overarching themes of ‘general recovery’ and ‘gastrointestinal symptoms’ were identified. General recovery included three themes: ‘life impact’, ‘mental impact’, including anxiety, and ‘physical impact’, including fatigue. Gastrointestinal symptoms included three themes: ‘abdominal symptoms’ such as pain, ‘diet and appetite’ and ‘expulsory function’, such as stool frequency. A total of 18 gastrointestinal symptoms were identified during patient recovery—many of which lasted several weeks following discharge.ConclusionThis study reports a range of gastrointestinal and nongastrointestinal symptoms experienced by patients during early gastrointestinal recovery. Identified symptoms have been synthesized into a conceptual framework to enable development of a definitive PROM for early gastrointestinal recovery.